1968
DOI: 10.1530/jrf.0.0170433
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Action of Intra-Amniotic Hypertonic Saline Treatment in Rabbits

Abstract: A study was made into the effects of hypertonic saline upon the intra-uterine pressure in non-pregnant and pregnant rabbits. In non-pregnant rabbits intra-luminal administration of hypertonic saline caused an almost immediate transient increase in amplitude and frequency of uterine pressure cycles, a response which was abolished by prior treatment with progesterone. In pregnant rabbits, provided all placentae were damaged by the treatment, intra-amniotic administration of 20% NaCl resulted in abortion of all f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1972
1972
1998
1998

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In rabbits (and goats), the corpus luteum secretes progesterone throughout pregnancy (13), so that a disorder in placental progesterone secretion will not adversely affect the pregnancy. In these animals, placental choriogonadotropin is needed to maintain the maternal corpus luteum, but the placenta is not needed to produce progesterone (14). By contrast in human beings, the corpus luteum secretes progesterone only during the first trimester; placental progesterone becomes sufficient to maintain pregnancy only after about 6 weeks gestation; the so-called "luteoplacental shift" (13,15).…”
Section: Nicole Glaser and Dennismentioning
confidence: 99%
“…In rabbits (and goats), the corpus luteum secretes progesterone throughout pregnancy (13), so that a disorder in placental progesterone secretion will not adversely affect the pregnancy. In these animals, placental choriogonadotropin is needed to maintain the maternal corpus luteum, but the placenta is not needed to produce progesterone (14). By contrast in human beings, the corpus luteum secretes progesterone only during the first trimester; placental progesterone becomes sufficient to maintain pregnancy only after about 6 weeks gestation; the so-called "luteoplacental shift" (13,15).…”
Section: Nicole Glaser and Dennismentioning
confidence: 99%
“…It has further been demonstrated that the fetal portion of the placenta is the most important component of the conceptus in maintaining luteal P 4 production. Removal of the fetus and placenta results in luteal regression, whereas removal of the fetus alone has no effect on P 4 production [2,[5][6][7][8]. The factor(s) produced by the conceptus that is responsible for maintaining P 4 production has not yet been fully identified or characterized, although previous investigators have reported identification of a potential placental luteotropin using a cultured luteinized granulosa cell bioassay system…”
Section: Introductionmentioning
confidence: 99%
“…Corpora lutea of the pregnant rabbit require the pres¬ ence of the fetal placenta to maintain progesterone production throughout pregnancy (Chu, Lee & You, 1946;Porter, Becker & Csapo, 1968;Holt & Ewing, 1974;Lanman & Thau, 1979). It is not known, however, whether the effect of the feto-placental unit is antiluteolytic and/or luteotrophic or whether it is exerted locally and/or systemically.…”
Section: Introductionmentioning
confidence: 99%